Prevalence and audiological features in carriers of GJB2 mutations, c.35delG and c.101T>C (p.M34T), in a UK population study. Issue 4 (31st July 2012) - Hall, Amanda; Pembrey, Marcus; Lutman, Mark; Steer, Colin; Bitner-Glindzicz, Maria
Abstract : Objectives: To determine the carrier rate of the GJB2 mutation c.35delG and c.101T>C in a UK population study; to determine whether carriers of the mutation had worse hearing or otoacoustic emissions compared to non-carriers. Design: Prospective cohort study. Setting: University of Bristol, UK. Participants: Children in the Avon Longitudinal Study of Parents and Children. 9202 were successfully genotyped for the c.35delG mutation and c.101>T and classified as either carriers or non-carriers. Outcome measures: Hearing thresholds at age 7, 9 and 11 years and otoacoustic emissions at age 9 and 11. Results: The carrier frequency of the c.35delG mutation was 1.36% (95% CI 1.13 to 1.62) and c.101T>C was 2.69% (95% CI 2.37 to 3.05). Carriers of c.35delG and c.101T>C had worse hearing than non-carriers at the extra-high frequency of 16 kHz. The mean difference in hearing at age 7 for the c.35delG mutation was 8.53 dB (95% CI 2.99, 14.07) and 12.57 dB at age 9 (95% CI 8.10, 17.04). The mean difference for c.101T>C at age 7 was 3.25 dB (95% CI −0.25 to 6.75) and 7.61 dB (95% CI 4.26 to 10.96) at age 9. Otoacoustic emissions were smaller in the c.35delG mutation carrier group: at 4 kHz the mean difference was −4.95 dB (95% CI −6.70 to −3.21) at age 9 and −3.94 dB (95% CI −5.78 to −2.10) at age 11. There was weak evidence for differences in otoacoustic emissions amplitude for c.101T>C carriers. Conclusion: Carriers of the c.35delG mutation and c.101T>C have worse extra-high-frequency hearing than non-carriers. This may be a predictor for changes in lower-frequency hearing in adulthood. The milder effects observed in carriers of c.101T>C are in keeping with its classification as a mutation causing mild/moderate hearing loss in homozygosity or compound heterozygosity.